Crianças nascidas expostas ao HIV sob a perspectiva da orfandade e da institucionalização - Costa, Ênia (2010)
Two decades after the beginning of the AIDS epidemic, it has been observed how one generation of children has been affected by HIV. They experience a childhood marked by their parent’s becoming ill, by being orphans and by the stigma caused by the illness. Some of these children whether they are the virus’ bearer or not have to be taken to institutions. Thus, living in an institution is, most of the times, the most viable option for the children. It was intended to analyze how children who were born exposed to HIV live inserted in support houses/orphanages in Fortaleza, Ceará. The option chosen was the articulation of the research with the qualitative and quantitative approach which was used to provide elements of the way the case study should follow. The modality of thematic oral history research was also used. The population used was composed of 24 children exposed to HIV on birth that live in full or part-time system in two institutions (support house and orphanage). The study was carried out during the first semester of 2010, in Fortaleza-Ceará, Northeastern region of Brazil. Two institutions registered in a public organ and which function as reference institutions in the state of Ceará, are responsible by the children’s care of children exposed to HIV on birth or infected during their lives. Both took part in the study: the “Casa do Sol Nascente” [House of Rising Sun (full-time permanence)] and the “Centro de Convivência Madre Regina” [Social Center Madre Regina (semi-full permanence)]. To collect the data were used: interviews semi-structured to collect epidemiologic, clinical and social data of the children and their parents; primary data obtained from the children’s health registers; life stories produced by the people in charge of the institutions and by the mothers and reports of prejudice situations experienced by the children. For the quantitative analysis, the institutions were compared by means of distribution of bivariad frequencies. It was observed that the children have access to the items indispensable for their adequate growth and development, facing, however, important markers of vulnerability. The differences between the two institutions were most of the time attributed to the mother’s presence in the care dedicated to the children of the semi-full time institutions. An inter-sectional work should be suggested and a full-time care according to the needs characteristic of each institution, each family and each child, in a more humanized resolute practice as a way of promoting life.